SENSITIVITAS JUMLAH STAGES PADA DESAIN ESP SUMUR DIRECTIONAL”X” LAPANGAN SALAWATI - Jeanne A.; Leonardo D. M.; Praditya N. (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
An Onshore Well “X” of JOB Pertamina-Petrochina field is a directional well. This particular well has ESP as the artificial lift to deliver the production fluid into the surface. Due to “off down hole”, the oil production had been suspended since 2012. However recently, the well will be activated and the pump will be modified into the new one. The purpose of this modification is to find the most suitable and effective pump with optimum numbers of installed stages on the ESP. This ESP design is started by nodal system analysis which corelates Inflow Performance Relationship (IPR) to Intake Pump Pressure. From the calculation using Pudjo Soekarno equation results a maximum flow rate in this well is 446,33 BPD. The flow rate is targeted to 65% from the maximum flowrate. Therefore, ESP series 319 NBV 250-500/60 Hz is chosen considering the operating range around 231-416 BPD which in this case is inside the range. Pump will be installed at 8500 ft depth. The numbers of stages based on calculation is 270 stages capable to lift 300 barrels fluid per day. This flowrate approximately meets the targeted flowrate, furthermore the pump will be at 47,9% of its Best Efficiency (BEP) during the operation. With this result the pump is considered able to operate efficiently and durably.